The mystery of zombie enterprises: "stiff but deathless" - Xinfeng Jiang; Sihai Li; Xianzhong Song (China Journal of Accounting Research, 2017)
Drawing on social exchange theory, this study uses data on China's Shanghai and Shenzhen A-share listed companies from 2009 to 2016 to examine why zombie enterprises are "stiff but deathless." We find that these enterprises are able to "linger breathlessly" due to government support in the form of increased subsidies and bank loans. The government is more inclined to grant subsidies to zombie companies that assume greater policy burdens, specifically those offering more jobs. Furthermore, an enterprise's property rights do not influence the level of "blood transfusions" received, and government assistance fails to bolster operating efficiency or value. This phenomenon is further explored in the context of the incentives local government officials have to maintain employment stability. Our conclusions highlight the necessity and urgency of cleaning up zombie enterprises.
Keywords: 650; Zombie enterprise; Government subsidy; Enterprise contribution; Private interests of officials; Enterprise value